Post - conflict land administration :a facilitator of the post - conflict state building in the case of Timor - Leste - Todorovski, Dimo (2020)
There is a growing recognition that land administration has a fundamental role to play in the post-conflict contexts. This paper observes land administration in the broader post-conflict state building in the case of Timor-Leste.